2003
DOI: 10.1097/00002030-200302140-00005
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of vaginal PRO 2000 gel in sexually active HIV-uninfected and abstinent HIV-infected women

Abstract: PRO 2000 Gel was safe and well tolerated in sexually active HIV-uninfected and sexually abstinent HIV-infected women, enabling the product to be considered for evaluation in efficacy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 18 publications
5
71
0
Order By: Relevance
“…Micronized CAP has shown to adsorb and inactivate HIV-1, HSV and other STIs (118). Earlier studies indicate that a gel formulation of micronized CAP has the potential to be used for topical intravaginal delivery of microbicides for prevention of STIs and HIV (119). It is converted into a gel and therefore does not have to be removed following its application (119).…”
Section: A Micronized Cellulose Acetate Phthalate Gel Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronized CAP has shown to adsorb and inactivate HIV-1, HSV and other STIs (118). Earlier studies indicate that a gel formulation of micronized CAP has the potential to be used for topical intravaginal delivery of microbicides for prevention of STIs and HIV (119). It is converted into a gel and therefore does not have to be removed following its application (119).…”
Section: A Micronized Cellulose Acetate Phthalate Gel Formulationmentioning
confidence: 99%
“…Earlier studies indicate that a gel formulation of micronized CAP has the potential to be used for topical intravaginal delivery of microbicides for prevention of STIs and HIV (119). It is converted into a gel and therefore does not have to be removed following its application (119). CAP is one of the potential anti-HIV vaginal gel formulations that are under Phase II clinical trials (120).…”
Section: A Micronized Cellulose Acetate Phthalate Gel Formulationmentioning
confidence: 99%
“…Phase 1 trials of PRO-2000 microbicide gel have revealed its safety and acceptability in healthy women (Smita et al, 2006). PRO-2000 microbicide gel is also well tolerated by HIV-infected women and men (Mayer et al, 2003;Tabet et al, 2003). Unfortunately, PRO-2000 gel showed only modest protection among women against HIV-1 in a phase 2/2b study (Abdool Karim et al, 2011).…”
Section: Synthesized Peptides and Polymersmentioning
confidence: 99%
“…These drugs encompass different mechanisms of action which require different drug targeting strategies for successful delivery (49)(50)(51)(52)(53)(54)(55). The mechanism of action of each microbicide agent will define the appropriate vaginal drug delivery system for those products.…”
Section: Microbicide Drug Candidatesmentioning
confidence: 99%
“…It has been demonstrated that PRO2000 is capable of protecting against HSV-2 in the mouse model (93), In these studies, the vaginal gel formulations used contained PRO 2000, Carbopol 1382, 0.05% lactic acid, and trolamine to adjust the pH to 4.5 (93). In a phase 1 study, the formulation was shown to be safe and tolerable to healthy volunteer women (94) and HIV-1 infected women (54). Although in a study comparing 2% and 4% formulations it was found that women exposed to the 4% gel product twice daily had more mild adverse events related to the genital tract than those women who were exposed to placebo or 2% formulation (54), PRO 2000 is currently being investigated in phase 2 and 3 clinical trials (95).…”
Section: Semisolids-hydrogelsmentioning
confidence: 99%